Bimodal Transitive Maps with Zero Topological Entropy - Al-shara'a, Iftichar; Naoum, Adil (Iraqi Journal of Science, 2024)
Our goal in this work is to describe the structure of a class of bimodal self maps on the compact real interval I with zero topological entropy and transitive.